The final run [videorecording (DVD)] - Waters, Drew, 1973-; Czura, Walter; Fahey, Jeff; Nelson, Judd (Level 33 Entertainment, 2025)
THE FINAL RUN is a gripping tale of sacrifice, redemption, and the lengths one man will go to protect those he loves. Starring Jeff Fahey, Judd Nelson, Drew Waters and introducing Maddie Henderson. A southern noir film inspired by true events from Operation Jackpot. Pierce Butler, a former Marine and long-retired marijuana smuggler must return to his old ways and make one final drug run to save his home, his company, and his sick wife.